Suicide note on the palm: Three case reports and discussion of medico-legal aspects. (April 2014) - Behera, C; Rautji, Ravi; Krishna, Karthik; Kumar, Avishek; Gupta, SK
Suicide notes are usually written by the victim on paper or readily accessible things such as notebooks, walls or mirrors. Though writing may be found on the body of the deceased, suicide notes in a structured manner written on the palm have not been reported in forensic literature. In all the three cases presented here, we found a handwritten note on the palm of the deceased at the time of autopsy. The victims had written a brief note in their own handwriting, citing the reasons for ending their lives. The suicide note in one case also mentioned details regarding the custody of the victim's children to be given to her mother. Since we have not found similar cases in the literature, we present and discuss our three cases herein.